Prospective randomized study of surgical treatment of pilonidal sinus; primary midline closure after elliptical excision versus rhomboid excision with limberg flap reconstruction versus open excision and healing by secondary intention - Kumar, Rajneesh; Hastir, Ankur; Walia, Ramandeep S.; Goyal, Subhash; Kaur, Amandeep (International Surgery Journal, 2017)
Background: Best surgical treatment of pilonidal sinus is always challenging for a surgeon in term of recurrence. Evaluation of surgical treatment of pilonidal sinus; primary midline closure after elliptical excision versus rhomboid excision with limberg flap reconstruction versus open excision and healing by secondary intention of sacrococcygeal pilonidal disease. Methods: In this prospective randomized study of 75 patients of sacrococcygeal pilonidal sinus were divided into 3 equal groups through randomly assigning the type of surgery. 25 patients of each group. Group I was operated by primary midline closure after elliptical excision, Group II rhomboid excision with limberg flap reconstruction and Group III open excision and healing by secondary intention. Results: Data was assessed between three groups in term of operative time, healing time and recurrence over a follow up period of 1 year. Mean operative time in group I (primary midline closure after elliptical excision) was 38.7±5.1 minutes, group II (Rhomboid excision with Limberg flap reconstruction) was 124.2±5.6 minutes, group III (Open excision and healing by secondary intention) was 20.6±5.6 minutes. Mean healing time for group I was 19.0±7.4 days, for group II was 17.0±8.0 days and for group III was 60±9.6 days. Recurrence occurred in 3 patients in group I and nil in group II and III. Conclusions: Rhomboid excision with limberg flap reconstruction is better choice than primary midline closure after elliptical excision and open excision in terms of healing time and reoccurrence in cases of sacrococcygeal pilonidal sinus.